2022
DOI: 10.3389/fmars.2022.970858
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic effects of short-term exercise on muscle texture and gut flora in the hybrid (Megalobrama amblycephala♀ × Ancherythroculter nigrocauda♂)

Abstract: Fillet texture plays a significant role in consumer acceptance, which heavily influenced by exercise according to previous studies. “Xianfeng No. 2”, a novel hybrid of Megalobrama amblycephala (M. amblycephala) (♀) and Ancherythroculter nigrocauda (A. nigrocauda) (♂), with characteristics of quick growth, good disease resistance, and anti-stress capability, is one of an important aquaculture fish species in China, however, the ways to improve fillet quality in this species remains unknown. In this study, a sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 95 publications
2
0
0
Order By: Relevance
“…amblycephala  Ancherythroculter nigrocauda) in moderate speed (1.2 body lengths [bl]/s) of water significantly increased flesh texture in terms of hardness, gumminess, cohesiveness, and chewiness. 241 Similar results were obtained in qingbo (Spinibarbus sinensis) after sustained exercise for 8 weeks. 237 Both studies noted that exercise significantly increased myofiber density and the proportions of smalldiameter fibres, indicating the stimulation of myocyte hyperplasia.…”
Section: Exercise Trainingsupporting
confidence: 68%
See 1 more Smart Citation
“…amblycephala  Ancherythroculter nigrocauda) in moderate speed (1.2 body lengths [bl]/s) of water significantly increased flesh texture in terms of hardness, gumminess, cohesiveness, and chewiness. 241 Similar results were obtained in qingbo (Spinibarbus sinensis) after sustained exercise for 8 weeks. 237 Both studies noted that exercise significantly increased myofiber density and the proportions of smalldiameter fibres, indicating the stimulation of myocyte hyperplasia.…”
Section: Exercise Trainingsupporting
confidence: 68%
“… 246 Recent work reported that short‐term (12‐16d) culture of hybrid ( Megalobrama. amblycephala × Ancherythroculter nigrocauda ) in moderate speed (1.2 body lengths [bl]/s) of water significantly increased flesh texture in terms of hardness, gumminess, cohesiveness, and chewiness 241 . Similar results were obtained in qingbo ( Spinibarbus sinensis ) after sustained exercise for 8 weeks 237 .…”
Section: Strategies To Regulate Texture Characteristics In Aquaculturesupporting
confidence: 56%